TRANSLATION USED IN TEACHING WRITING PROCEDURE TEXT AT SMA YPK MEDAN - Nurul Fatma; Sumarsih Sumarsih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study aimed at describing translation used and reason in teaching writing procedure text at SMA YPK Medan. This study was qualitatively conducted that taken 3 English teachers of SMA YPK Medan. The data were collected by using an interview and observing the whole process of teaching writing procedure text. The findings of this study showed that there were 59 times of using translation found during three processes that they were conveying and checking the meaning of words or sentences, explaining the grammar and classroom management. It was also found that translation used in the scientific approach activity that experimenting, associating and communicating activity in teaching. The reason of using translation in teaching writing procedure text were facilitating communication, teacher-student relationship and the L2 learning. The findings of this study revealed that translation contributed to the study of foreign language teaching especially teaching writing skills.